Media and Digital Management - Noam, Eli M. (Springer, 2019)
This book is a college-level version of a longer volume aimed at graduate courses and the professional market. The basics are shared because the subject matter and its significance are the same. Everybody understands the importance of the media and information sector. It is a growing and dynamic field, encompassing content creation, distribution platforms and technology devices. The information industry sector in 2017 accounted for about $1.7 trillion in the USA and $6 trillion worldwide, about 6% of global gross domestic product (GDP). As a share of “discretionary income,” the share of the sector is closer to 20%; as a share of “discretionary time,” it is an extraordinary 30%. Per capita media consumption in the USA is 2100 hours annually, which translates to 5.7 hours per day. And it is not only quantity that counts. Media industries are also a driver of change, leading in technological innovation, testing new organizational practices, and transforming societal institutions and culture. Thus, there is no dispute over the centrality of the sector in advanced and developing economies and societies.